Increased Production and Marketing of Crackers Through Process Improvements in SR Crackers Home Industries in Wonosari Jember - Umilasari, Reni; Nurhalimah, Nurhalimah; Rahman, Miftahur (Kontribusia : Research Dissemination for Community Development, 2019)
Along with the increase in culinary business units offering various types of food in Jember Regency, the consumption of crackers has also increased. This is because the habits of the Indonesian people, especially in Jember Regency, make crackers as one of the complementary foods on every menu that should not be missed when dining. With the Community Partnership Program activity organized by the PKM Muhammadiyah University Jember team and the SR Crackers Home Industry Partner (IRT) SR has an impact on increasing the income of workers, making crackers faster and varied and reducing unemployment, especially Wonosari villagers can be recruited as workers if increased production capacity. The final target to be achieved is the establishment of a cracker production business unit with appropriate technology, namely with a cracker printing machine, and marketing management with the help of information technology such as market places and social media.